1985
DOI: 10.1111/j.1398-9995.1985.tb02677.x
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the Prick Test

Abstract: The different needles and methods used in the prick test give rise to disparate results. This has significance when carrying out multi-centre studies and when using the technique in the standardization of allergenic extracts. With test reliability as our objective, prick tests were carried out on 30 subjects: 10 patients sensitive to Dermatophagoides pteronyssinus received a glycerine extract of known allergenic potency, 10 healthy individuals 2.5% codeine phosphate in a glycerine solution, and another 10, his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 2 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Results have been expressed as mean diameter [4], positive or negative, with positive defined as mean diameter/-> 3 mm [1,8,9] or > 0 mm [10], and as area [11]. Allergen wheal diameter greater than 0.4 of 3 mg/ml histamine dihydrochloride wheal diameter [12] has been advocated and allergen area adjusted for histamine and negative controls [13] has been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results have been expressed as mean diameter [4], positive or negative, with positive defined as mean diameter/-> 3 mm [1,8,9] or > 0 mm [10], and as area [11]. Allergen wheal diameter greater than 0.4 of 3 mg/ml histamine dihydrochloride wheal diameter [12] has been advocated and allergen area adjusted for histamine and negative controls [13] has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Any recommendations will not necessarily apply to all epidemiological studies as methods of skin prick testing change, and several studies have reported differing wheal sizes between methods [11,17]. Results from different methods may therefore not be directly comparable.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations performed have been described in a previous study [5] and included forced expiratory volume in one second (FEV 1 ), forced vital capacity (FVC), FEV 1 / FVC, a peak expiratory flow diary, skin prick testing using the skin prick/puncture technique [6] and reversibility testing to β 2 agonists [7]. A bronchial challenge test to histamine was also performed by the YAN technique [8].…”
Section: Methodsmentioning
confidence: 99%
“…Hypersensitivity reactions to penicillins are due to different metabolite formed in vivo when the antibiotic is administered 13. After the administration of PCN G, the β‐lactam ring irreversibly opens during nucleophilic attack, resulting in the formation of penicilloyl metabolites and the covalent binding to tissue macromolecules to produce the hapten‐protein complex and induce immune response.…”
mentioning
confidence: 99%